Dynamic Responses of Microglia in Animal Models of Multiple Sclerosis - Plastini, Melanie J.; Desu, Haritha L.; Brambilla, Roberta (Frontiers in Cellular Neuroscience, 2020)
Microglia play an essential role in the maintenance of central nervous system (CNS) homeostasis and its response to injury and disease. Most neurological disorders feature profound microglial rearrangements initiated with the purpose of containing damage and promote repair, but often resulting in overt inflammatory activation that sustains and propagates the neurodegenerative process. This is especially evident in multiple sclerosis (MS), often viewed as the prototypical neuroinflammatory disorder. Microglia is center stage in MS immunopathology, taking on varied roles depending upon location and disease phase. For this reason, microglial activation and microglia-driven neuroinflammation are considered as key events in the onset, progression and resolution of MS. Our understating of microglial functions in MS has widened exponentially in the last decade by virtue of the introduction of new tools that have allowed the discrimination of microglia from other myeloid populations, and the appreciation of their complex functional diversity. This, in combination with a variety of animal models that mimic specific features and processes of MS pathophysiology, has contributed to filling the gap of knowledge in the cascade of events underlying MS pathophysiology. The purpose of this review is to present the state of the art on the responses of microglia observed in the most commonly used animal models of MS, specifically the immune-mediated experimental autoimmune encephalomyelitis (EAE) model and the chemically-induced cuprizone and lysolecithin models. Coming to a clear understanding of the role, interplay, and regulation of microglia in these models is essential to identify emerging targets for therapy and direct drug discovery efforts.